The relational patterns of selected factors influencing the EFL college learners' reading comprehension - Nuriyatul Hamidah (Journal of Research on English and Language Learning (J-REaLL), 2021)
Having an effect on reading, metacognitive awareness, self-efficacy and motivation are considered as the main factor in affecting EFL reading comprehension. Thus, the aim of the present study is to investigate the relational pattern of those selected factors toward EFL reading comprehension and investigates the contribution of each variable. The design is categorized as quantitative study. The subjects of the study consisted of 90 students of the English Letters and Language, Humanity Faculty, UIN Maliki Malang. The instruments used in this study are a test and questionnaires. Moreover, the data are analyzed using multiple regression techniques including a correlation design called Path Analysis. The result of the study has shown that the regression model in the first layer is proven insignificant to the independent variable. The total contribution of all variables in the first layer is 2.5%. While, the regression model of second layer is proven significant. The total contribution of all variables in the path diagram in the second layer of this study is 44.86%. Based on the result, it is suggested for the future research to have a research on other factors such as combining affective and cognitive factors while considering students' diversity such proficiency level, personality and gender.